Monoclonal antibody targeting the β-barrel assembly machine of Escherichia coli is bactericidal - Storek, Kelly M. (Proc Natl Acad Sci U S A, 2018)
The folding and insertion of integral β-barrel membrane proteins into the outer membrane of Gram-negative bacteria is required for viability and bacterial pathogenesis. Unfortunately, the lack of selective and potent modulators to dissect β-barrel folding in vivo has hampered our understanding of this fundamental biological process. Here, we characterize a monoclonal antibody that selectively inhibits an essential component of the Escherichia coli β-barrel assembly machine, BamA. In the absence of complement or other immune factors, the unmodified antibody MAB1 demonstrates bactericidal activity against an E. coli strain with truncated LPS. Direct binding of MAB1 to an extracellular BamA epitope inhibits its β-barrel folding activity, induces periplasmic stress, disrupts outer membrane integrity, and kills bacteria. Notably, resistance to MAB1-mediated killing reveals a link between outer membrane fluidity and protein folding by BamA in vivo, underscoring the utility of this antibody for studying β-barrel membrane protein folding within a living cell. Identification of this BamA antagonist highlights the potential for new mechanisms of antibiotics to inhibit Gram-negative bacterial growth by targeting extracellular epitopes.